Thinking Process of Students of MTs Darul Hikmah in Mathematic Problem Solving on The Material of Flat Side Space Building Reviewed From Adversity Quotient - Mukhtasar, Mukhtasar; Asri, Khairul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to describe the thinking process of MTSs Darul Hikmah students in solving mathematical problems in flat side space building materials reviewed from Adversity Quotient. This study uses a descriptive type of research with a qualitative approach. The research began by providing an adversity response profile (ARP) questionnaire to 25 students in grade IX of MTSs Darul Hikmah. From these results, two subjects were obtained consisting of one climber and one camper subject. Furthermore, the two subjects were given problem solving test questions twice using flat-sided space building materials to measure students' thinking processes. Data collection was carried out through tests and interviews, while data analysis used qualitative data analysis techniques, namely data reduction and data presentation as well as drawing conclusions from each adversity quotient group. The results of the study show that the thinking process of MTsS Darul Hikmah students based on the adversity quotient in the climbers and campers categories has the same thinking process, namely the conceptual thinking process in solving mathematical problems in the building material of flat side spaces.